BIODIESEL PRODUCTION IN A PHOTOBIOREACTOR FROM MICROALGAE BIOMASS USING INDUSTRIAL EMISSIONS OF CARBON DIOXIDE - Erazo E., R. (2010)
Biodiesel is produced in a vertical photobioreactor using a Botryococcus braunii bubbling carbon dioxide in natural conditions of solar irradiation. The technique of metabolic control is applied in the growth of microalgae producing up to 14 g / L and 29% lipid of dry biomass. The oil is extracted with n-hexane and then by transesterification the biodiesel is obtained with a calorific value of 40 MJ/kg, a density of 0.86 kg/L and a viscosity of 5.2 × 10(-4) Pa s (at 40 °C)